Present Bias and Underinvestment in Education? Long-Run Effects of Childhood Exposure to Booms in Colombia - Carrillo, Bladimir (Journal of Labor Economics, 2020)
This paper examines the long-run impacts of income shocks by exploiting variation in coffee cultivation patterns within Colombia and world coffee prices during cohorts’ school-going years. The results indicate that cohorts that faced higher returns to coffee-related work in childhood completed fewer years of schooling and have lower adult earnings scores. Several pieces of evidence suggest that these results reflect changes in educational decisions induced by temporary changes in the opportunity cost of schooling. These findings are consistent with the possibility that students may ignore or heavily discount the future consequences of dropout decisions when faced with immediate income gains.